Utilization of natural alleles and haplotypes of Ctb1 for rice cold adaptability - Li, Lingling; Cheng, Gongye; Li, Wenyu; Zhang, Di; Yu, Jianghui; Zhou, Huang; Ding, Xiaoping; Wang, Zhijun; Zhu, Wanjing; Li, Jiajia; He, Jiwai; Duan, Meijuan; et al. (Gene, 2025)
•The InDel at −1,302  bp in the Ctb1 promoter enhances gene expression and cold tolerance.•The InDel improves rice cold adaptability at seedling and booting stages.•Incorporation of the InDel into NILs (NIL-Ctb1HapI) increases rice cold tolerance and yield.•The −1,302 fragment of InDel may be used as a marker for breeding cold-tolerant rice. Cold stress during the booting stage of rice (Oryza sativa) significantly reduces yields, particularly in temperate and high-altitude regions. This study investigates the Ctb1 gene, critical for booting-stage cold tolerance, to improve breeding of resilient rice varieties. Re-sequencing the Ctb1 promoter in 202 accessions identified six Insertions and/or deletions (InDels) and four Single nucleotide polymorphisms (SNPs), with an InDel at −1,302 bp significantly boosting Ctb1 expression and cold tolerance. Accessions carrying this InDel (Haplotype I) exhibited the highest tolerance. Near-isogenic lines (NIL-Ctb1HapI) introduced Haplotype I into the cold-sensitive Huazhan (HZ) variety, resulting in a 5.9-fold increase in Ctb1 expression, higher seedling survival, improved pollen fertility, a 64.2 % increase in seed setting rate, and a 12 g per plant yield boost under cold stress. These findings confirm the critical role of the −1,302 InDel in cold tolerance and establish NIL-Ctb1HapI as a valuable breeding tool for cold-resilient rice.